2010
DOI: 10.1136/emj.2010.103093
|View full text |Cite
|
Sign up to set email alerts
|

Mephedrone toxicity in a Scottish emergency department

Abstract: A profile of largely psychoactive and cardiovascular toxicity is described with drug naivety perhaps explaining the high rates of bingeing and addiction reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 9 publications
(10 reference statements)
3
54
1
Order By: Relevance
“…These results are consistent with previous studies in animal models, reporting that, it induces substantial increases in blood pressure, heart rate, and cardiac contractility (Meng et al, 2012), in addition to acute cardiovascular toxicity characterized by hypertension and tachycardia (Sivagnanam et al, 2013;Nicholson et al, 2010;Regan et al, 2011;Maskell et al, 2011;Wood et al, 2010). Moreover, mephedrone consistently results in mydriasis, a specific and acute effect also observed after MDMA and amphetamine administration de la Torre et al, 2000de la Torre et al, , 2004Mas et al, 1999), although slighter in comparison with MDMA.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous studies in animal models, reporting that, it induces substantial increases in blood pressure, heart rate, and cardiac contractility (Meng et al, 2012), in addition to acute cardiovascular toxicity characterized by hypertension and tachycardia (Sivagnanam et al, 2013;Nicholson et al, 2010;Regan et al, 2011;Maskell et al, 2011;Wood et al, 2010). Moreover, mephedrone consistently results in mydriasis, a specific and acute effect also observed after MDMA and amphetamine administration de la Torre et al, 2000de la Torre et al, , 2004Mas et al, 1999), although slighter in comparison with MDMA.…”
Section: Discussionsupporting
confidence: 93%
“…Although mephedrone was here identified on its own in the cause of death in only one-third of cases (n = 18, 30%), this finding confirms some of the concerns recently expressed regarding the acute toxicity potential of the drug itself (James et al, 2011;Maskell et al, 2011;Schifano et al, 2011;Torrance & Cooper, 2010;Regan et al, 2010). It could be argued that the fact there are such a relatively large number of deaths in a comparatively short period (two years) underlines the need to inform consumers of its potential to cause death on its own.…”
Section: Mephedrone Use With Other Substancessupporting
confidence: 80%
“…Nine of the patients in this series had laboratory confirmation of mephedrone ingestion [30]. In a retrospective review of self-reported exposures in a Scottish emergency department agitation was the most common symptom [35]. Similarly, in a prospective US series 66% were agitated [13].…”
Section: Subjective User Effectsmentioning
confidence: 99%